Visualization of constrained data by rational cubic ball function /Wan Zafira Ezza Wan Zakaria and Jamaludin Md Ali - Wan Zakaria, Wan Zafira; Md Ali, Jamaludin (2015)
The main purpose of this paper is the construction of shape preserving interpolation for visualization of constrained data that will be smooth and pleasant. Three shape parameters are introduced in order to control the shape of the interpolation. The rational cubic ball function is constructed according to the shape of the data that are constraint between two lines using appropriate conditions on each of the shape parameters. Numerical examples are provided to demonstrate that the anticipated scheme is interactive and smooth.